Implementasi Lean Warehousing untuk Meminimasi Waste di Gudang PT XYZ - Fitriyah, Jihan; Ernawati, Dira; Rahmawati, Nur (Universitas Batanghari Jambi, 2025)
The purpose of this study is to identify waste in the warehousing process using value stream mapping and provide suggestions for improvements to the efficiency of warehousing operations at PT XYZ. This study uses a lean warehousing approach with the value stream mapping method, process activity mapping, gemba shikumi, and 5 whys analysis. The results of this study concluded that improvements by simplifying the process activity mapping resulted in a reduction of 10 warehousing activities, for each type of activity, a reduction of 12 types of activities was obtained. Then the time obtained previously from 268,000 minutes became 266,384 minutes, thus saving 1,616 seconds or 26 minutes 56 seconds at PT XYZ.